Transnational education in Malaysia: does it prepare graduates for a globalized world? - Giridharan, Beena; Ling, Peter; Mazzolini, Margaret (Penerbit Universiti Kebangsaan Malaysia, 2015)
The establishment of higher educational hubs in Malaysia and Singapore has spurred the growth of transnational education offerings in Asia, and attracted foreign higher education providers to set up branch campuses in these countries. In this paper we ask whether transnational education as practiced in Malaysia has a particular contribution to one aspect of the student experience – preparing graduates for an increasingly globalized world (Urry 2002). We considered the contribution that internationalisation of curriculum and the international experience of students and staff bring to the development of graduate capabilities suited to a globalized world. The opportunities that transnational education bring to the learning experiences of students were studied. The paper reports on an empirical study conducted in Australia and on transnational campuses in Malaysia to illustrate the extent to which current educational practice equips students to operate beyond national boundaries and suggest what needs to happen in order to realize the potential of transnational education for preparing students to operate in a globalized environment.